More Effective Way to Perform Complete Percutaneous Vertebroplasty for Patients in Kummell’s Disease: A Case Report - Seung Hee Yoo; Ji Seon Chae; Minjin Lee; Bo Kyung Kang; Hahck Soo Park; Won-Joong Kim (The Ewha Medical Journal)
An 84-year-old woman visited our pain clinic with complaints of low back pain and severe radiating pain in the right lower extremity during walking. The patient demonstrated subacute compression fracture of L3 with vacuum change in lumbar spine plain radiographs and MRI which suggest Kummell’s disease. Despite our conservative treatments, she had little back pain relief. Therefore, we planned a percutaneous vertebroplasty. Manual compression could help perform percutaneous vertebroplasty more effectively by expanding the vertebral body. In addition, the spontaneous recovery of vacuum cleft width using negative pressure could help perform the technique more effectively. We successfully performed percutaneous vertebroplasty using these combination therapies for our patient.